2017
DOI: 10.1007/s10461-017-1701-1
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Changes Following Uptake of HIV Pre-exposure Prophylaxis Among Men Who Have Sex with Men in a Clinical Setting

Abstract: We describe changes in sexual behaviors among men who have sex with men (MSM) following initiation of pre-exposure prophylaxis (PrEP) in a clinic-based sample of MSM initiating PrEP in Providence, Rhode Island. Data were collected at baseline, 3, and 6 months following PrEP initiation including total number of anal sex partners and condom use. A longitudinal mixed effects model assessed changes in number of partners and condom use over time, adjusting for age, race, and education. There was no statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 13 publications
(21 reference statements)
0
34
1
3
Order By: Relevance
“…Although HIV self-testing may overcome some traditional barriers to HIV testing, such as stigma or logistical challenges, there may be unintended consequences associated with the use of the test, and these unintended consequences may depend on the strategy for HIV self-testing delivery. Changes in sexual behaviors have been considered following HIV prevention interventions including preexposure prophylaxis [ 3 , 4 ], male circumcision [ 5 ], and vaccination [ 6 ]. Among MSM, access to HIV self-testing has resulted in increased awareness of HIV risk, which may have led to reduced sexual risk-taking [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although HIV self-testing may overcome some traditional barriers to HIV testing, such as stigma or logistical challenges, there may be unintended consequences associated with the use of the test, and these unintended consequences may depend on the strategy for HIV self-testing delivery. Changes in sexual behaviors have been considered following HIV prevention interventions including preexposure prophylaxis [ 3 , 4 ], male circumcision [ 5 ], and vaccination [ 6 ]. Among MSM, access to HIV self-testing has resulted in increased awareness of HIV risk, which may have led to reduced sexual risk-taking [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we did not model behavioral risk compensation, such as a decrease in condom use or an increase in partner acquisition rate, for agents initiating PrEP. An early study of MSM initiating PrEP in Rhode Island indicated a higher number of partnerships within which condomless anal sex occurred but not an overall increase in the number of partners over the first 6 months of follow-up [ 47 ]. We also did not implement the (approximately) 3-month HIV screening interval among MSM agents on PrEP, who continue in the model to test stochastically at the background rate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a recent meta‐analysis, individuals starting PrEP have a high burden of STIs . Furthermore, there is emerging evidence from open‐label and demonstration studies and implementation sites among gay, bisexual and other men who have sex with men (MSM) that condom use decreases among some men on PrEP, particularly among those already engaging in condomless sex or other high‐risk behaviours . However, modelling among MSM suggest that if PrEP is accompanied by regular STI services, increased detection and treatment may mitigate increases in STI transmission .…”
Section: Discussionmentioning
confidence: 99%